2014
DOI: 10.1057/ap.2014.12
|View full text |Cite
|
Sign up to set email alerts
|

Macroeconomics, economic crisis and electoral outcomes: A national European pool

Abstract: An abundance of comparative survey research argues the presence of economic voting as an individual force in European elections, thereby refuting a possible ecological fallacy. But the hypothesis of economic voting at the aggregate level, with macroeconomics influencing overall electoral outcomes, seems less sure. Indeed, there might be a micrological fallacy at work, with the supposed individual economic vote effect not adding up to a national electoral effect after all. Certainly that would account for the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
78
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 96 publications
(85 citation statements)
references
References 50 publications
5
78
2
Order By: Relevance
“…This reward-punishment axiom has led Anderson (2007, p. 277) to note that "given citizens limited willingness and capacity to process complex information about politics, rewards and punishment should most easily be detectable with regard to the performance of the economy-after all, the economy is perhaps the most perennially talked-about issue". The economy is especially likely to be salient during an economic crisis (Dassonneville & Lewis-Beck, 2014;Singer, 2011). If we couple this with the fact that ideologically motivated voting has been declining, fewer citizens now have a predisposition to vote for a particular party (e.g.…”
Section: Defining the Mechanisms Of Economic Voting In Ep Electionsmentioning
confidence: 99%
See 1 more Smart Citation
“…This reward-punishment axiom has led Anderson (2007, p. 277) to note that "given citizens limited willingness and capacity to process complex information about politics, rewards and punishment should most easily be detectable with regard to the performance of the economy-after all, the economy is perhaps the most perennially talked-about issue". The economy is especially likely to be salient during an economic crisis (Dassonneville & Lewis-Beck, 2014;Singer, 2011). If we couple this with the fact that ideologically motivated voting has been declining, fewer citizens now have a predisposition to vote for a particular party (e.g.…”
Section: Defining the Mechanisms Of Economic Voting In Ep Electionsmentioning
confidence: 99%
“…Dassonneville & Lewis-Beck, 2014;Duch & Stevenson, 2008;Lewis-Beck & Paldam, 2000;Lewis-Beck & Stegmaier, 2013). During economic crises, the economy becomes even more salient (Dassonneville & Lewis-Beck, 2014;Singer, 2011), as the media gives greater coverage to the issue (Soroka, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Examples of this are: PASOK, the Greek Socialist Party, that was all but annihilated in the May 2012 election, and, among others, Labour (UK, 2010), PSOE (Spain, 2011), CDA (Netherlands, 2010) and Venstre (Denmark, 2011) -all suffered major electoral losses and lost control of the government. Several studies indeed demonstrate that voters have punished their governments for the economic crisis and its consequences (Palmer and Whitten, 2011;Rattinger and Steinbrecher, 2011;Anderson and Hecht, 2012;Marsh and Mikhaylov, 2012;Nezi, 2012;Bartels, 2014;Fraile and Lewis-Beck, 2014;Kriesi, 2014;Dassonneville and Lewis-Beck, 2014). These findings fit into the larger framework of so-called economic voting.…”
Section: Introductionmentioning
confidence: 85%
“…Economic crises threaten the well-being of people, and they become better informed about the state of the economy (Krosnick 1990;Krosnick and Kinder 1990;Miller and Krosnick 2000), which increases the salience of the economy for voters in general (Singer 2011;Singer 2013;Traber et al 2018), and specifically for their voting decision (Gomez and Wilson 2006;Anderson 2007). Indeed, recent research confirms that economic voting took place during the recent economic crisis (Palmer and Whitten 2011;Rattinger and Steinbrecher 2011;Anderson and Hecht 2012;Bellucci et al 2012;Marsh and Mikhaylov 2012;Nezi 2012;Bartels 2014;Fraile and Lewis-Beck 2014;Kriesi 2014;Dassonneville and Lewis-Beck 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Even though multiparty systems and coalition governments in Europe obscure clarity of responsibility (Powell and Whitten 1993), previous research has indicated strong economic effects in elections across Europe (Duch and Stevenson 2008;Lewis-Beck and Stegmaier 2000;Lewis-Beck 2006;van der Brug, van der Eijk and Franklin 2007). Furthermore, a general negativity bias among voters and in the media leads to the expectation that economic effects are even more pronounced in times of crisis (Bloom and Price 1975;Dassonneville and Lewis-Beck 2014a;Soroka 2006). …”
Section: Introductionmentioning
confidence: 99%